2002
DOI: 10.1006/jcta.2001.3207
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relations and Schauder Bases

Abstract: The concept of inter-changes of Schauder bases is used to interpret inverse relations for sequences. For a given power series, the interplay between different representations by Schauder bases can result in combinatorial identities, new or known. Local cohomology residues and local duality are used for computations. The viewpoint of Riordan arrays is examined using Schauder bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It is shown in [7,Theorem 2.1] that an inverse relation with the orthogonal property comes from representations of a power series by two Schauder bases in the sense of [7]. Assume that all principal filters on X are finite.…”
Section: Schauder Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown in [7,Theorem 2.1] that an inverse relation with the orthogonal property comes from representations of a power series by two Schauder bases in the sense of [7]. Assume that all principal filters on X are finite.…”
Section: Schauder Basesmentioning
confidence: 99%
“…An inversion formula is regarded as a phenomenon of change of 'coordinate systems'. It is shown that Lagrange inversion [5], MacMahon's master theorem [4, Example 1], Saalschütz's theorem [6,Identity 11] and Dixon's theorem [6,Identity 12] are phenomena of changes of variables; an inverse relation is a phenomenon of a change of Schauder bases [7]; Jacobi's formula is a phenomenon of a change of parameters [9]. The purpose of this article is to show that Möbius inversion for a locally finite partially ordered set is within the same view.…”
Section: Introductionmentioning
confidence: 99%
“…The Riordan group was introduced, under this name and in a more restrictive context, by L. Shapiro and collaborators in [35]. Since then, many authors have developed this topic [14,22,27,37,40,42]. Some previous related results can be found in [2,16,17,32,33,39].…”
Section: Introductionmentioning
confidence: 99%
“…Since his work a number of methods for finding matrix inversions have been developed, among which the following are worthwhile mentioning: the integral representation approach (Egorychev [19]); the umbral calculus (Roman [46]); the operator method (Krattenthaler [36]); the local cohomology residues over Schauder-bases (Huang [33]); the Riordan group and array (Shapiro and Sprugnoli [41,42,53,57]); the telescopic approach on formal factorials (Chu [14,13]); the recurrence relation method (Milne and Bhatnagar [43]). Further reference may also extend to [6,7] concerning the U (n)-extensions of inverse relations on root systems, and to [48] as to the theory of rather general Möbius-Rota inversions over partially ordered sets.…”
Section: Introductionmentioning
confidence: 99%